a) Ta có:
\(\frac{a}{b}=\frac{11a}{11b}\) và \(\frac{c}{d}=\frac{9c}{9d}\)
Mà \(\frac{a}{b}=\frac{c}{d}\) nên suy ra \(\frac{a}{b}=\frac{11a}{11b}=\frac{9c}{9d}\)
=> \(\frac{a}{b}=\frac{11a+9c}{11b+9d}\)
\(\text{a) Ta có: }\)
\(\frac{a}{b}=\frac{11a}{11b}\)\(\text{và }\)\(\frac{c}{d}=\frac{9c}{9d}\)
\(\text{Ma dau bai cho}\) \(\frac{a}{b}=\frac{c}{d}\) \(\Rightarrow\)\(\frac{a}{b}=\frac{11a}{11b}=\frac{9c}{9d}\)
\(\text{Vay }\)\(\frac{a}{b}=\frac{11a+9c}{11b+9d}\)
dựa vào công thức 2 phân số bằng nhau
a)\(\frac{a}{b}=\frac{11a+9c}{11b+9d}\)
do \(\frac{a}{b}=\frac{c}{d}\)nên \(\frac{11a+9c}{11b+9d}=\frac{a\times\left(11+9\right)}{b\times\left(11+9\right)}\)
\(\Rightarrow\)tự làm tiếp đi